NURSING TEAM PERCEPTION ON SPIRITUALITY IN END-OF-LIFE CARE - Brener Santos Silva; Elbert Eddy Costa; Iêda Glória de Souza Picasso e Silva Gabriel; Alexandre Ernesto Silva; Richardson Miranda Machado (Universidade Federal do Paraná, 2016)
The objective was to investigate the nursing team's perception on spirituality in end-of-life care. A qualitative and descriptive study was undertaken with 20 nursing professionals from a hospital in the Central-West of Minas Gerais. The data were collected between May and June 2014 at the oncology sector by means of a semistructured questionnaire. The data were analyzed using the content analysis technique. The results appoint that, although the nursing team accepts death well, spirituality is hardly discussed and there is still a lack of preparation to address this aspect in end-of-life care. Based on these findings, the theme needs to be included in the curricula of higher and technical nursing education and further research in the area is needed to sensitize and train the professionals.